Why do we need a Professional Ambulance Service? - Maharjan, Dhiresh Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Nepal lacks pre-hospital emergency care system , victims of trauma or medical emergencies in Kathmandu are transported to hospital either by taxi or private vehicle, with no medical care en route. Since there is no three-digit emergency phone number, such as 999 in the UK or 911 in the US, many patients are not transported to hospital in time for meaningful medical intervention. Many patients suffer grievous complications or even die as a result. According to a study by Patan Hospital, of patients arriving at emergency rooms, only 10% arrive by ambulance while 54% arrive by taxi.